PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN DENGAN KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING PADA TOKO SEMBAKO BAROKAH DIBESUKI SITUBONDO - Andika, Roni; Kusnadi, Edy; Wiryaningtyas, Dwi Perwitasari (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
The problems faced by entrepreneurs are not only how these entrepreneurs provide services and promote their place of business, but what is no less important is how an entrepreneur can survive or even excel in business competition. The purpose of this study was to analyze and test the effect of product quality and service quality on consumer satisfaction at the Barokah Grocery Store through purchasing decisions. The population in this study were consumers at Barokah Grocery Store. The sampling technique was determined by quota sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that product quality has a significant positive effect on purchasing decisions, service quality has a significant positive effect on purchasing decisions, product quality has a significant positive effect on consumer satisfaction, service quality has no significant effect on consumer satisfaction, decision purchases have a negative effect on consumer satisfaction. The results of the indirect hypothesis test show that product quality on purchasing decisions through consumer satisfaction has a significant negative effect, service quality on purchasing decisions through consumer satisfaction has no significant effect.